Polyimide precursor, polyimide and polyimide film and their preparation method and application

By introducing fluorine-containing groups into the polyimide material and a unit structure that can rotate axially along the chain segment, the technical difficulties of colorless transparent polyimide material in terms of dimensional stability, hygroscopic resistance and bending resistance are solved, and the material's high transparency, good thermal properties and high bending resistance are achieved.

CN114106322BActive Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202010893274.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-08-31
Publication Date
2025-03-04
Estimated Expiration
2040-08-31

AI Technical Summary

Technical Problem

The existing colorless transparent polyimide materials are difficult to meet technical requirements such as dimensional stability, hygroscopic resistance and bending resistance at the same time.

Method used

By introducing fluorine-containing groups and unit structures that can rotate axially along the segment, a rigid coplanar molecular structure is formed to improve the elasticity and hygroscopicity of the material.

Benefits of technology

It realizes the high transparency, good thermal performance, low water absorption and high bending resistance of polyimide materials, and is suitable for substrate materials of flexible display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114106322B_ABST
    Figure CN114106322B_ABST
Patent Text Reader

Abstract

The present invention discloses a polyimide precursor, a polyimide and a colorless transparent polyimide film, as well as a preparation method and application thereof. The polyimide precursor contains at least one of the structural unit shown in formula (1), the structural unit shown in formula (2), the structural unit shown in formula (3), the structural unit shown in formula (4), and at least one of the structural unit shown in formula (5), the structural unit shown in formula (6), the structural unit shown in formula (7), and the structural unit shown in formula (8), wherein R1 and R2 are each independently a fluorine-containing aromatic residue containing at least one carbon six-membered ring, and R1 and R2 are the same or different. The light transmittance of the polyimide film of the present invention is greater than 85%, the glass transition temperature is greater than 350°C, and the water absorption is less than 1%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyimide, in particular to a polyimide precursor, polyimide and a colorless transparent polyimide film, as well as a preparation method and application thereof. Background Art

[0002] Polyimide is a type of polymer with excellent comprehensive properties, such as excellent heat resistance, low temperature resistance, self-lubrication, radiation resistance and flame retardancy, as well as excellent mechanical and dielectric properties. It is widely used in aerospace, microelectronics, solar cells, high temperature filtration, machinery, separation membranes and OLED. It is worth mentioning that with the rapid development of flexible electronics and flexible display technology, transparent PI film has become the preferred material for flexible display device substrates due to its excellent high temperature resistance, good mechanical properties and excellent chemical stability.

[0003] Traditional aromatic PI has a strong conjugation effect in its molecular structure. A charge transfer complex (CTC) is formed between the dianhydride and diamine units of adjacent molecular chains, making the film appear brownish yellow, which results in insufficient transparency in the blue-violet and ultraviolet bands. Currently, yellow transparent PI has begun to be widely used in flexible display devices. In contrast, although colorless transparent PI film has greater development potential as a flexible display substrate, the existing colorless transparent PI materials need to meet the technical requirements of low moisture absorption and bending resistance while meeting transparency and thermal properties in order to be truly applied.

[0004] Ordinary polyimide main chains contain a large number of imide ring structures. Due to electronic polarization and crystallinity, there are strong forces between polyimide molecular chains, which makes the polyimide molecular chains densely stacked, making them difficult to dissolve and melt and difficult to process, which seriously affects their application value. In order to solve the problem of solubility, the precursor of polyimide, polyamic acid solution, is usually synthesized first, and then processed into polyamic acid material by coating or spinning, and then converted into the final polyimide material by thermal imidization or chemical imidization. The processing and performance of polyimide materials are directly related to the quality of the precursor solution. Usually, polyamic acid is usually prepared by reacting dianhydride and diamine in a non-protonic polar solvent at low temperature. There are many types of dianhydride and diamine monomers, and the raw material sources are wide. Different monomer combinations can be polymerized to obtain polyimide materials with different structures, resulting in differences in the performance of polyimide materials.

[0005] The research on colorless and transparent PI film mainly starts from the monomer structure, introduces strong polar groups or large side group structure monomers or uses aliphatic monomers, thereby inhibiting the formation of intramolecular / intermolecular charge transfer complexes (CTC) to achieve the purpose of transparency of polyimide. But at the same time, since this type of molecular structure has a certain influence on the stability of the molecular chain, the thermal and mechanical properties of the resulting film will be reduced. In addition, if polar groups are introduced, the hygroscopicity of the film will be greatly improved. Therefore, balancing the relationship between the transmittance, thermal properties, hygroscopicity and mechanical properties of the PI film, while meeting the transparency requirements, maintaining the excellent thermal properties of PI itself, and improving the film's anti-hygroscopicity and bending resistance are the key to the research of PI film materials for substrates. Summary of the invention

[0006] One of the technical problems to be solved by the present invention is that it is difficult for colorless and transparent polyimide in the prior art to simultaneously meet technical problems such as dimensional stability, moisture absorption resistance and bending resistance. Therefore, a polyimide precursor is provided. The polyimide formed by the precursor is mainly composed of a rigid coplanar molecular structure, which ensures the thermal properties of the material. At the same time, a unit structure that can rotate along the axial direction of the chain segment is added to improve the elasticity of the material and increase the bending resistance of the polyimide. In addition, the introduction of fluorine-containing groups in the chain segment can reduce the surface energy of the material and achieve an anti-hygroscopic effect.

[0007] The second technical problem to be solved by the present invention is to provide a method for preparing a polyimide precursor corresponding to solving one of the above technical problems.

[0008] The third technical problem to be solved by the present invention is to provide a polyimide corresponding to solving one of the above technical problems.

[0009] The fourth technical problem to be solved by the present invention is to provide a polyimide film and a preparation method thereof corresponding to solving one of the above technical problems.

[0010] The fifth technical problem to be solved by the present invention is to provide an application of the polyimide film corresponding to solving one of the above technical problems.

[0011] One of the objects of the present invention is to provide a polyimide precursor comprising at least one of the structural unit represented by formula (1), the structural unit represented by formula (2), the structural unit represented by formula (3), and the structural unit represented by formula (4), and at least one of the structural unit represented by formula (5), the structural unit represented by formula (6), the structural unit represented by formula (7), and the structural unit represented by formula (8).

[0012] The structural units represented by formula (1), formula (2), formula (3), formula (4), formula (5), formula (6), formula (7) and formula (8) are as follows:

[0013]

[0014]

[0015]

[0016]

[0017]

[0018]

[0019]

[0020]

[0021] Wherein R1 and R2 are each independently a fluorine-containing aromatic residue containing at least one carbon six-membered ring, and R1 and R2 are the same or different.

[0022] In the polyimide precursor, at least one of the structural units represented by formula (1), the structural units represented by formula (2), the structural units represented by formula (3), and the structural units represented by formula (4) accounts for 10 to 90% of the total molar number of the structural units, preferably 20 to 80%, more preferably 25 to 75%, and more preferably 30 to 70%.

[0023] In the technical solution of the present invention, preferably, R1 and R2 are each independently any one of the following groups,

[0024] The second object of the present invention is a method for preparing the polyimide precursor, comprising the following steps:

[0025] (a) dissolving a diamine monomer containing an R1 group and / or a diamine monomer containing an R2 group in an organic solvent to obtain a diamine monomer solution;

[0026] (b) adding 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride and 2,3,3',4'-biphenyltetracarboxylic acid dianhydride to the diamine monomer solution to react and obtain a polyimide precursor;

[0027] or including,

[0028] (a) dissolving a diamine monomer containing an R1 group and / or a diamine monomer containing an R2 group in an organic solvent to obtain a diamine monomer solution;

[0029] (b) adding 1,2,3,4-cyclobutanetetracarboxylic dianhydride to the diamine monomer solution obtained in step (a), and reacting to obtain a polyamic acid solution A;

[0030] (c) Same as step (a);

[0031] (d) adding 2,3,3',4'-biphenyltetracarboxylic dianhydride to the diamine monomer solution obtained in step (c), and reacting to obtain a polyamic acid solution B;

[0032] (e) Mixing solution A and solution B to obtain a polyimide precursor.

[0033] In the reaction involved in step b or step b and step d described above, the reaction temperature is preferably -5 to 60°C, more preferably 10 to 50°C; the reaction time is preferably 2 to 48 hours, more preferably 4 to 24 hours.

[0034] In the technical solution of the present invention, preferably, the ratio of the total molar amount of the dianhydride monomer to the total molar amount of the diamine monomer is (0.8-1.2):1, preferably (0.9-1.1):1;

[0035] 1,2,3,4-cyclobutanetetracarboxylic dianhydride accounts for 10 to 90% of the total molar amount of the dianhydride monomer, preferably 20 to 80%, more preferably 25 to 75%, and more preferably 30 to 70%;

[0036] The total solid content of the dianhydride monomer and the diamine monomer in the solution is 5 to 50% wt, preferably 10 to 40% wt, and more preferably 10 to 30% wt.

[0037] In the technical scheme of the present invention, preferably, the diamine monomer is selected from at least one of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl, 4,4'-diamino-2,2'-bis(trifluoromethoxy)biphenyl, 4,4'-diamino-3,3'-bis(trifluoromethoxy)biphenyl, 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-bis(3-aminophenyl)hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2-bis(3-hydroxy-4-aminophenyl)hexafluoropropane, 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether, 3,3'-bis(trifluoromethyl)-4,4'-diaminophenyl ether and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane.

[0038] In the above technical solution, the organic solvent can be a good solvent for polyamic acid, including but not limited to at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.

[0039] It can be seen from the preparation method of the polyimide precursor of the present invention that at least one structural unit of formula (1), formula (2), formula (3) and formula (4) contained in the polyimide precursor of the present invention is derived from the reaction of the diamine monomer with 1,2,3,4-cyclobutanetetracarboxylic dianhydride; and at least one structural unit of formula (5), formula (6), formula (7) and formula (8) contained in the polyimide precursor of the present invention is derived from the reaction of the diamine monomer with 2,3,3',4'-biphenyltetracarboxylic dianhydride.

[0040] The third object of the present invention is to provide a polyimide comprising at least one of the structural unit represented by formula (9) and the structural unit represented by formula (10), and at least one of the structural unit represented by formula (11) and the structural unit represented by formula (12),

[0041]

[0042]

[0043]

[0044]

[0045] wherein R1 and R2 are each independently a fluorinated aromatic residue containing at least one carbon six-membered ring, and R1 and R2 are the same or different;

[0046] In the polyimide, the structural unit represented by formula (9) and the structural unit represented by formula (10) account for 10 to 90% of the total molar number of the structural units, preferably 20 to 80%, more preferably 25 to 75%, and more preferably 30 to 70%.

[0047] In the technical solution of the present invention, preferably, R1 and R2 are each independently any one of the following groups,

[0048]

[0049]

[0050] The polyimide of the present invention is obtained by subjecting the polyimide precursor or the polyimide precursor obtained by the preparation method to thermal imidization.

[0051] A fourth object of the present invention is to provide a polyimide film comprising the polyimide described above.

[0052] The polyimide film has a thickness of 5 to 300 μm, preferably 8 to 200 μm.

[0053] The thickness uniformity of the polyimide film is less than 5%, and the surface roughness is less than 1 nm.

[0054] The polyimide film of the present invention is obtained by subjecting the polyimide precursor or the polyimide precursor obtained by the preparation method to thermal imidization.

[0055] A fifth object of the present invention is to provide a method for preparing the polyimide film, comprising the following steps:

[0056] (a) preparing a polyimide precursor solution;

[0057] (b) Casting or spin coating the polyimide precursor solution to obtain a polyamic acid wet film, and obtaining the polyimide film after pre-baking and thermal imidization.

[0058] In the above step (a), the solvent in the solution includes but is not limited to at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.

[0059] In the above step (a), the concentration of the solution is 5 to 50% wt, preferably 10 to 40% wt, and more preferably 10 to 30% wt.

[0060] In the above step (b), the pre-baking temperature is 50-150°C, preferably 60-120°C;

[0061] In the above step (b), the temperature of the thermal imidization is 150-500°C, preferably 150-400°C.

[0062] The sixth object of the present invention is to provide the application of the polyimide film in substrates for display screens, substrates for glass window color-changing glass, and substrates for solar cells, but is not limited to the above applications.

[0063] Compared with the prior art, the advantages of the present invention are:

[0064] The present invention selects 1,2,3,4-cyclobutanetetracarboxylic dianhydride and fluorine-containing aromatic diamine with relatively stable structure as main monomers to obtain The structure can inhibit the formation of charge transfer complexes (CTC) within and between polyimide molecules, thereby ensuring the transparency of the material. At the same time, the introduction of fluorinated groups can greatly reduce the surface energy of the material, thereby achieving a hydrophobic effect. However, due to the strong rigidity of this structure, the film prepared is usually brittle and has poor bending resistance, which greatly affects the application of the material. Therefore, a certain amount of The structure increases the flexibility of the material without affecting the transparency of the material, and greatly improves the material's anti-bending ability. In addition, the polyimide film obtained by the present invention has very good thickness uniformity and a very flat surface morphology. Such a film is not prone to defects and can greatly improve the mechanical properties of the material.

[0065] The polyimide film obtained by the above method has a light transmittance greater than 85%, a glass transition temperature greater than 350° C., a curvature radius less than 1 mm, can withstand more than 200,000 bendings, and a water absorption rate less than 1%. DETAILED DESCRIPTION

[0066] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0067] The raw materials used in the specific implementation manner of the present invention are commercially available.

[0068] [Example 1]

[0069] 1. Preparation of stock solution: 2.56 kg of 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl and 0.67 kg of 2,2-bis(4-aminophenyl)hexafluoropropane were stirred and dissolved in 31.05 kg of N,N-dimethylacetamide (DMAc) at 25°C. After complete dissolution, 0.88 kg of 2,3,3',4'-biphenyltetracarboxylic dianhydride and 1.37 kg of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA) were added. After fully stirring for 24 hours, a polyimide precursor was obtained. The polyimide precursor was filtered through 5 μm and 0.5 μm filter membranes in turn and then degassed under reduced pressure to obtain a polyimide film-forming stock solution.

[0070] 2. Cast film: The film-forming stock solution is extruded through the film head, the wet film thickness is controlled to be 500μm, and the film is cast on a smooth steel belt.

[0071] 3. Pre-baking treatment: The film-forming stock solution is passed through an 85°C hot furnace under a nitrogen flow atmosphere to remove most of the solvent to obtain a self-supporting polyamic acid film.

[0072] 4. Thermal imidization: The polyamic acid film is subjected to multi-stage thermal imidization to obtain a high-performance polyimide film, which is sequentially subjected to imidization at the first temperature zone of 170°C, the second temperature zone of 250°C, and the third temperature zone of 300°C, and then slitting and winding.

[0073] Microscopic observation showed that the surface of the PI film was smooth and free of defects. The tested film had excellent thickness uniformity, a total light transmittance of 92%, a glass transition temperature of 355°C, a curvature radius of less than 1mm, and could withstand more than 200,000 bends. The water absorption rate was 0.8%.

[0074] [Example 2]

[0075] 1. Preparation of stock solution: 3.20 kg of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl was stirred and dissolved in 30.37 kg of N-methylpyrrolidone (NMP) at 25°C. After complete dissolution, 0.59 kg of 2,3,3',4'-biphenyltetracarboxylic acid dianhydride and 1.57 kg of 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride (CBDA) were added. After fully stirring for 24 hours, a polyimide precursor was obtained. The polyimide precursor was filtered through 5 μm and 0.5 μm filter membranes in turn and then degassed under reduced pressure to obtain a polyimide film-forming stock solution.

[0076] 2. Cast film: The film-forming stock solution is extruded through the film head, the wet film thickness is controlled to be 500μm, and the film is cast on a smooth steel belt.

[0077] 3. Pre-baking treatment: The film-forming stock solution is passed through an 85°C hot furnace under a nitrogen flow atmosphere to remove most of the solvent to obtain a self-supporting polyamic acid film.

[0078] 4. Thermal imidization: The polyamic acid film is subjected to multi-stage thermal imidization to obtain a high-performance polyimide film, which is sequentially subjected to imidization at the first temperature zone of 170°C, the second temperature zone of 250°C, and the third temperature zone of 300°C, and then slitting and winding.

[0079] Microscopic observation showed that the surface of the PI film was smooth and free of defects. The tested film had excellent thickness uniformity, a total light transmittance of 92%, a glass transition temperature of 350°C, a curvature radius of less than 1mm, and could withstand more than 200,000 bends. The water absorption rate was 0.6%.

[0080] [Example 3]

[0081] 1. Preparation of stock solution: 3.52 kg of 4,4'-diamino-2,2'-bis(trifluoromethoxy)-p-diaminobiphenyl was stirred and dissolved in 33.15 kg of N,N-dimethylacetamide (DMAC) at 25°C. After complete dissolution, 1.15 kg of 2,3,3',4'-biphenyltetracarboxylic acid dianhydride and 1.18 kg of 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride (CBDA) were added. After fully stirring for 24 hours, a polyimide precursor was obtained. The polyimide precursor was filtered through 5 μm and 0.5 μm filter membranes in turn and then degassed under reduced pressure to obtain a polyimide film-forming stock solution.

[0082] 2. Cast film: The film-forming stock solution is extruded through the film head, the wet film thickness is controlled to be 500μm, and the film is cast on a smooth steel belt.

[0083] 3. Pre-baking treatment: The film-forming stock solution is passed through an 85°C hot furnace under a nitrogen flow atmosphere to remove most of the solvent to obtain a self-supporting polyamic acid film.

[0084] 4. Thermal imidization: The polyamic acid film is subjected to multi-stage thermal imidization to obtain a high-performance polyimide film, which is sequentially subjected to imidization at the first temperature zone of 170°C, the second temperature zone of 250°C, and the third temperature zone of 300°C, and then slitting and winding.

[0085] Microscopic observation showed that the surface of the PI film was smooth and free of defects. The tested film had excellent thickness uniformity, a total light transmittance of 89%, a glass transition temperature of 360°C, a curvature radius of less than 1mm, and could withstand more than 200,000 bends. The water absorption rate was 0.6%.

[0086] [Example 4]

[0087] 1. Preparation of stock solution: 3.52 kg of 4,4'-diamino-2,2'-bis(trifluoromethoxy)-p-diaminobiphenyl was stirred and dissolved in 33.15 kg of N,N-dimethylacetamide (DMAC) at 25°C. After complete dissolution, 0.29 kg of 2,3,3',4'-biphenyltetracarboxylic acid dianhydride and 1.78 kg of 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride (CBDA) were added. After fully stirring for 24 hours, a polyimide precursor was obtained. The polyimide precursor was filtered through 5 μm and 0.5 μm filter membranes in turn and then degassed under reduced pressure to obtain a polyimide film-forming stock solution.

[0088] 2. Cast film: The film-forming stock solution is extruded through the film head, the wet film thickness is controlled to be 500μm, and the film is cast on a smooth steel belt.

[0089] 3. Pre-baking treatment: The film-forming stock solution is passed through an 85°C hot furnace under a nitrogen flow atmosphere to remove most of the solvent to obtain a self-supporting polyamic acid film.

[0090] 4. Thermal imidization: The polyamic acid film is subjected to multi-stage thermal imidization to obtain a high-performance polyimide film, which is sequentially subjected to imidization at the first temperature zone of 170°C, the second temperature zone of 250°C, and the third temperature zone of 300°C, and then slitting and winding.

[0091] Microscopic observation showed that the surface of the PI film was smooth and free of defects. The tested film had excellent thickness uniformity, a total light transmittance of 89%, a glass transition temperature of 353°C, a curvature radius of less than 1mm, and could withstand more than 200,000 bends. The water absorption rate was 0.7%.

[0092] [Example 5]

[0093] 1. Preparation of stock solution: 3.20 kg of 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl was stirred and dissolved in 33.15 kg of N,N-dimethylacetamide (DMAC) at 25°C. After complete dissolution, 2.06 kg of 2,3,3',4'-biphenyltetracarboxylic acid dianhydride and 0.59 kg of 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride (CBDA) were added. After fully stirring for 24 hours, a polyimide precursor was obtained. The polyimide precursor was filtered through 5 μm and 0.5 μm filter membranes in turn and then degassed under reduced pressure to obtain a polyimide film-forming stock solution.

[0094] 2. Cast film: The film-forming stock solution is extruded through the film head, the wet film thickness is controlled to be 500μm, and the film is cast on a smooth steel belt.

[0095] 3. Pre-baking treatment: The film-forming stock solution is passed through an 85°C hot furnace under a nitrogen flow atmosphere to remove most of the solvent to obtain a self-supporting polyamic acid film.

[0096] 4. Thermal imidization: The polyamic acid film is subjected to multi-stage thermal imidization to obtain a high-performance polyimide film, which is sequentially subjected to imidization at the first temperature zone of 170°C, the second temperature zone of 250°C, and the third temperature zone of 300°C, and then slitting and winding.

[0097] Microscopic observation showed that the surface of the PI film was smooth and free of defects. The tested film had excellent thickness uniformity, a total light transmittance of 85%, a glass transition temperature of 393°C, a curvature radius of less than 1mm, and could withstand more than 200,000 bends. The water absorption rate was 0.6%.

[0098] [Example 6]

[0099] 1. Preparation of stock solution: 3.20 kg of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl was stirred and dissolved in 22.40 kg of N,N-dimethylacetamide (DMAC) at 25°C. After complete dissolution, 1.18 kg of 2,3,3',4'-biphenyltetracarboxylic acid dianhydride and 1.22 kg of 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride (CBDA) were added. After fully stirring for 24 hours, a polyimide precursor was obtained. The polyimide precursor was filtered through 5 μm and 0.5 μm filter membranes in turn and then degassed under reduced pressure to obtain a polyimide film-forming stock solution.

[0100] 2. Cast film: The film-forming stock solution is extruded through the film head, the wet film thickness is controlled to be 500μm, and the film is cast on a smooth steel belt.

[0101] 3. Pre-baking treatment: The film-forming stock solution is passed through an 85°C hot furnace under a nitrogen flow atmosphere to remove most of the solvent to obtain a self-supporting polyamic acid film.

[0102] 4. Thermal imidization: The polyamic acid film is subjected to multi-stage thermal imidization to obtain a high-performance polyimide film, which is sequentially subjected to imidization at the first temperature zone of 170°C, the second temperature zone of 250°C, and the third temperature zone of 300°C, and then slitting and winding.

[0103] Microscopic observation showed that the surface of the PI film was smooth and free of defects. The tested film had excellent thickness uniformity, a total light transmittance of 89%, a glass transition temperature of 388°C, a curvature radius of less than 1mm, and could withstand more than 200,000 bends. The water absorption rate was 0.6%.

[0104] [Example 7]

[0105] 1. Preparation of stock solution: 3.20 kg of 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl was stirred and dissolved in 53.46 kg of N,N-dimethylacetamide (DMAC) at 25°C. After complete dissolution, 2.35 kg of 2,3,3',4'-biphenyltetracarboxylic acid dianhydride and 0.39 kg of 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride (CBDA) were added. After fully stirring for 24 hours, a polyimide precursor was obtained. The polyimide precursor was filtered through 5μm and 0.5μm filter membranes in turn and then degassed under reduced pressure to obtain a polyimide film-forming stock solution.

[0106] 2. Cast film: The film-forming stock solution is extruded through the film head, the wet film thickness is controlled to be 500μm, and the film is cast on a smooth steel belt.

[0107] 3. Pre-baking treatment: The film-forming stock solution is passed through an 85°C hot furnace under a nitrogen flow atmosphere to remove most of the solvent to obtain a self-supporting polyamic acid film.

[0108] 4. Thermal imidization: The polyamic acid film is subjected to multi-stage thermal imidization to obtain a high-performance polyimide film, which is sequentially subjected to imidization at the first temperature zone of 170°C, the second temperature zone of 250°C, and the third temperature zone of 300°C, and then slitting and winding.

[0109] Microscopic observation showed that the surface of the PI film was smooth and free of defects. The tested film had excellent thickness uniformity, a total light transmittance of 85%, a glass transition temperature of 403°C, a curvature radius of less than 1mm, and could withstand more than 200,000 bends. The water absorption rate was 0.6%.

[0110] [Example 8]

[0111] 1. Preparation of stock solution: 3.20 kg of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl was stirred and dissolved in 30.88 kg of N,N-dimethylacetamide (DMAC) at 25°C. After complete dissolution, 0.88 kg of 2,3,3',4'-biphenyltetracarboxylic acid dianhydride and 1.37 kg of 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride (CBDA) were added. After fully stirring for 24 hours, a polyimide precursor was obtained. The polyimide precursor was filtered through 5 μm and 0.5 μm filter membranes in turn and then degassed under reduced pressure to obtain a polyimide film-forming stock solution.

[0112] 2. Cast film: The film-forming stock solution is extruded through the film head, the wet film thickness is controlled to be 500μm, and the film is cast on a smooth steel belt.

[0113] 3. Pre-baking treatment: The film-forming stock solution is passed through an 85°C hot furnace under a nitrogen flow atmosphere to remove most of the solvent to obtain a self-supporting polyamic acid film.

[0114] 4. Thermal imidization: The polyamic acid film is subjected to multi-stage thermal imidization to obtain a high-performance polyimide film, which is sequentially subjected to imidization at the first temperature zone of 170°C, the second temperature zone of 250°C, and the third temperature zone of 300°C, and then slitting and winding.

[0115] Microscopic observation showed that the surface of the PI film was smooth and free of defects. The tested film had excellent thickness uniformity, a total light transmittance of 89%, a glass transition temperature of 385°C, a curvature radius of less than 1mm, and could withstand more than 200,000 bends. The water absorption rate was 0.6%.

[0116] [Example 9]

[0117] 1. Preparation of stock solution: 2.56 kg of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl and 0.70 kg of 4,4'-diamino-2,2'-bis(trifluoromethoxy)-p-diaminobiphenyl were stirred and dissolved in 32.36 kg of N,N-dimethylacetamide (DMAC) at 25°C. After complete dissolution, 1.47 kg of 2,3,3',4'-biphenyltetracarboxylic acid dianhydride and 0.98 kg of 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride (CBDA) were added. After fully stirring for 24 hours, a polyimide precursor was obtained. The polyimide precursor was filtered through 5 μm and 0.5 μm filter membranes in turn and then degassed under reduced pressure to obtain a polyimide film-forming stock solution.

[0118] 2. Cast film: The film-forming stock solution is extruded through the film head, the wet film thickness is controlled to be 500μm, and the film is cast on a smooth steel belt.

[0119] 3. Pre-baking treatment: The film-forming stock solution is passed through an 85°C hot furnace under a nitrogen flow atmosphere to remove most of the solvent to obtain a self-supporting polyamic acid film.

[0120] 4. Thermal imidization: The polyamic acid film is subjected to multi-stage thermal imidization to obtain a high-performance polyimide film, which is sequentially subjected to imidization at the first temperature zone of 170°C, the second temperature zone of 250°C, and the third temperature zone of 300°C, and then slitting and winding.

[0121] Microscopic observation showed that the surface of the PI film was smooth and free of defects. The tested film had excellent thickness uniformity, a total light transmittance of 90%, a glass transition temperature of 393°C, a curvature radius of less than 1mm, and could withstand more than 200,000 bends. The water absorption rate was 0.7%.

[0122] [Example 10]

[0123] 1. Preparation of stock solution: 3.20 kg of 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl was dissolved in 34.62 kg of N,N-dimethylacetamide (DMAC) at 25°C with stirring. After complete dissolution, 2.91 kg of 2,3,3',4'-biphenyltetracarboxylic dianhydride was added and stirred for 24 hours to obtain polyimide precursor 1.

[0124] 3.20 kg of 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl was dissolved in 29.13 kg of N,N-dimethylacetamide (DMAC) under stirring at 25°C. After the mixture was completely dissolved, 1.94 kg of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA) was added and the mixture was stirred for 24 hours to obtain a polyimide precursor 2.

[0125] 12.22 kg of precursor 1 and 23.99 kg of precursor 2 were fully mixed to obtain polyimide precursor 3.

[0126] The polyimide precursor 3 was filtered through 5 μm and 0.5 μm filter membranes in sequence and then degassed under reduced pressure to obtain a polyimide film-forming stock solution.

[0127] 2. Cast film: The film-forming stock solution is extruded through the film head, the wet film thickness is controlled to be 500μm, and the film is cast on a smooth steel belt.

[0128] 3. Pre-baking treatment: The film-forming stock solution is passed through an 85°C hot furnace under a nitrogen flow atmosphere to remove most of the solvent to obtain a self-supporting polyamic acid film.

[0129] 4. Thermal imidization: The polyamic acid film is subjected to multi-stage thermal imidization to obtain a high-performance polyimide film, which is sequentially subjected to imidization at the first temperature zone of 170°C, the second temperature zone of 250°C, and the third temperature zone of 300°C, and then slitting and winding.

[0130] Microscopic observation showed that the surface of the PI film was smooth and free of defects. The tested film had excellent thickness uniformity, a total light transmittance of 90%, a glass transition temperature of 389°C, a curvature radius of less than 1mm, and could withstand more than 200,000 bends. The water absorption rate was 0.6%.

[0131] [Comparative Example 1]

[0132] 3.2 kg of 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl was stirred and dissolved in 31.62 kg of N-methylpyrrolidone (NMP) at 25°C. After complete dissolution, 0.59 kg of 3,3',4,4'-biphenyl tetracarboxylic dianhydride and 1.79 kg of 1,2,4,5-cyclohexane tetracarboxylic dianhydride (HPMDA) were added to obtain a polyamic acid film-forming stock solution, which was cast into a film and imidized to obtain a polyimide film. The polyimide film had a total light transmittance of 90%, a glass transition temperature of 328°C, a radius of curvature of 3 mm, and a water absorption of 1.5%.

[0133] [Comparative Example 2]

[0134] 1.08 kg of p-phenylenediamine was stirred and dissolved in 18.36 kg of N-methylpyrrolidone (NMP) at 25°C. After complete dissolution, 0.59 kg of 3,3′,4,4′-biphenyltetracarboxylic dianhydride and 1.57 kg of cyclobutanetetracarboxylic dianhydride (CBDA) were added to obtain a polyamic acid film-forming stock solution, which was cast into a film and imidized to obtain a polyimide film. The polyimide film had a total light transmittance of 73%, a glass transition temperature of 400°C, a radius of curvature of 8 mm, and a water absorption of 2.6%.

Claims

1. A polyimide precursor comprising at least one of the structural unit represented by the following formula (1), the structural unit represented by the following formula (2), the structural unit represented by the following formula (3), and the structural unit represented by the following formula (4), and at least one of the structural unit represented by the following formula (5), the structural unit represented by the following formula (6), the structural unit represented by the following formula (7), and the structural unit represented by the following formula (8), wherein R1 and R2 are each independently a fluorinated aromatic residue containing at least one carbon six-membered ring, and R1 and R2 are the same or different; At least one of the structural unit represented by formula (1), the structural unit represented by formula (2), the structural unit represented by formula (3) and the structural unit represented by formula (4) accounts for 10 to 90% of the total molar number of the structural units; R1 and R2 are each independently any one of the following groups, 2. The polyimide precursor according to claim 1, characterized in that: At least one of the structural unit represented by formula (1), the structural unit represented by formula (2), the structural unit represented by formula (3) and the structural unit represented by formula (4) accounts for 20 to 80% of the total molar number of the structural units.

3. The polyimide precursor according to claim 2, characterized in that: At least one of the structural unit represented by formula (1), the structural unit represented by formula (2), the structural unit represented by formula (3) and the structural unit represented by formula (4) accounts for 25 to 75% of the total molar number of the structural units.

4. The polyimide precursor according to claim 3, characterized in that: At least one of the structural unit represented by formula (1), the structural unit represented by formula (2), the structural unit represented by formula (3) and the structural unit represented by formula (4) accounts for 30 to 70% of the total molar number of the structural units.

5. A method for preparing a polyimide precursor according to any one of claims 1 to 4, comprising the following steps: (a) dissolving a diamine monomer containing an R1 group and / or a diamine monomer containing an R2 group in an organic solvent to obtain a diamine monomer solution; (b) adding 1,2,3,4-cyclobutanetetracarboxylic dianhydride and 2,3,3',4'-biphenyltetracarboxylic dianhydride to the diamine monomer solution to react and obtain the polyimide precursor; or including, (a) dissolving a diamine monomer containing an R1 group and / or a diamine monomer containing an R2 group in an organic solvent to obtain a diamine monomer solution; (b) adding 1,2,3,4-cyclobutanetetracarboxylic dianhydride to the diamine monomer solution obtained in step (a), and reacting to obtain a polyamic acid solution A; (c) Same as step (a); (d) adding 2,3,3',4'-biphenyltetracarboxylic dianhydride to the diamine monomer solution obtained in step (c), and reacting to obtain a polyamic acid solution B; (e) Mixing solution A and solution B to obtain a polyimide precursor.

6. The method for preparing a polyimide precursor according to claim 5, characterized in that: The ratio of the total molar amount of the dianhydride monomer to the total molar amount of the diamine monomer is (0.8-1.2):1; and / or, The 1,2,3,4-cyclobutanetetracarboxylic dianhydride accounts for 10 to 90% of the total molar amount of the dianhydride monomer; and / or, The total solid content of the dianhydride monomer and the diamine monomer in the solution is 5 to 50%w; and / or, The organic solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide; and / or, The reaction temperature of the reaction is -5 to 60°C; and / or, The reaction time of the reaction is 2 to 48 hours.

7. The method for preparing a polyimide precursor according to claim 6, characterized in that: The ratio of the total molar amount of the dianhydride monomer to the total molar amount of the diamine monomer is (0.9-1.1):1; and / or, The 1,2,3,4-cyclobutanetetracarboxylic dianhydride accounts for 20 to 80% of the total molar amount of the dianhydride monomer; and / or, The total solid content of the dianhydride monomer and the diamine monomer in the solution is 10-40%wt.

8. The method for preparing a polyimide precursor according to claim 7, characterized in that: The 1,2,3,4-cyclobutanetetracarboxylic dianhydride accounts for 25-75% of the total molar amount of the dianhydride monomer; and / or, The total solid content of the dianhydride monomer and the diamine monomer in the solution is 10-30%wt.

9. The method for preparing a polyimide precursor according to claim 8, characterized in that: The 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride accounts for 30-70% of the total molar amount of the dianhydride monomer.

10. The method for preparing a polyimide precursor according to claim 5, characterized in that: The diamine monomer is selected from at least one of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl, 4,4'-diamino-2,2'-bis(trifluoromethoxy)biphenyl, 4,4'-diamino-3,3'-bis(trifluoromethoxy)biphenyl, 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-bis(3-aminophenyl)hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2-bis(3-hydroxy-4-aminophenyl)hexafluoropropane, 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether, 3,3'-bis(trifluoromethyl)-4,4'-diaminophenyl ether, and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane.

11. A polyimide comprising at least one of the structural unit represented by the following formula (9) and the structural unit represented by the following formula (10), and at least one of the structural unit represented by the following formula (11) and the structural unit represented by the following formula (12): Wherein R1 and R2 are fluorinated aromatic residues containing at least one carbon six-membered ring, and R1 and R2 are the same or different; The structural unit represented by formula (9) and the structural unit represented by formula (10) account for 10 to 90% of the total molar number of the structural units; The R1 and R2 are each independently any one of the following groups, 12. The polyimide according to claim 11, characterized in that: The structural unit represented by formula (9) and the structural unit represented by formula (10) account for 20 to 80% of the total molar number of the structural units.

13. The polyimide according to claim 12, characterized in that: The structural unit represented by formula (9) and the structural unit represented by formula (10) account for 25 to 75% of the total molar number of the structural units.

14. The polyimide according to claim 13, characterized in that: The structural unit represented by formula (9) and the structural unit represented by formula (10) account for 30 to 70% of the total molar number of the structural units.

15. The polyimide according to any one of claims 11 to 14, which is obtained by subjecting the polyimide precursor according to any one of claims 1 to 4 or the polyimide precursor obtained by the preparation method according to any one of claims 5 to 10 to thermal imidization. A polyimide film comprising the polyimide according to claim 15 .

17. The polyimide film according to claim 16, characterized in that: The polyimide film is obtained by thermal imidization of the polyimide precursor described in any one of claims 1 to 4 or the polyimide precursor obtained by the preparation method described in any one of claims 5 to 10.

18. A method for preparing the polyimide film according to claim 16 or 17, comprising the following steps: (a) preparing a polyimide precursor solution; (b) Casting or spin coating the polyimide precursor solution to obtain a polyamic acid wet film, and obtaining the polyimide film after pre-baking and thermal imidization.

19. The method for preparing a polyimide film according to claim 18, characterized in that: In the step (b), the pre-baking temperature is 50-150° C.; and / or, In the step (b), the temperature of the thermal imidization is 150-500°C.

20. The method for preparing a polyimide film according to claim 19, characterized in that: In the step (b), the pre-baking temperature is 60-120° C.; and / or, In the step (b), the temperature of the thermal imidization is 150-400°C.

21. Use of the polyimide film according to claim 16 or 17 in substrates for display screens, substrates for color-changing glass for glass windows, and substrates for solar cells.

Citation Information

Patent Citations

  • Colorless transparent polyimide film with stable size and preparation method thereof

    CN111087812A